2014
DOI: 10.1371/journal.pone.0107832
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Signaling Activation by Post-Ischemia Treatment with Astragaloside IV Attenuates Myocardial Ischemia-Reperfusion Injury

Abstract: In this study, we evaluated the effect of astragaloside IV (Ast IV) post-ischemia treatment on myocardial ischemia-reperfusion (IR) injury (IRI). We also examined whether hypoxia inducible factor-1α (HIF-1α) and its downstream gene-inducible nitric oxide (NO) synthase (iNOS) play roles in the cardioprotective effect of Ast IV. Cultured cardiomyocytes and perfused isolated rat hearts were exposed to Ast IV during reperfusion in the presence or absence of the HIF-1α inhibitor 2-methoxyestradiol (2-MeOE2). The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…HIF‐1α, as the first response to ischemia in cellular level, is closely associated with a great deal of signaling pathway, such as HIF‐1α/iNOS and PI3K/Akt/HIF‐1α . Treatment with AS‐IV (50 μ m , 4 h) during the postischemia period also obviously increased the expression of HIF‐1α, iNOS, and Bcl‐2 and reduced the caspase‐3 expression and LDH release in IRI cardiomyocytes and isolated heart . Under the hypoxia condition, AS‐IV (25–50 μg/mL/31.8–63.6 μ m ) demonstrated the potent protective effect of cardiomyocytes via upregulating the expression and the activity of SOD‐1 and inhibiting the ROS and MDA under the physiological and hypoxic status in the cytoplasm .…”
Section: Pharmacological Effect Of Astragaloside IVmentioning
confidence: 99%
“…HIF‐1α, as the first response to ischemia in cellular level, is closely associated with a great deal of signaling pathway, such as HIF‐1α/iNOS and PI3K/Akt/HIF‐1α . Treatment with AS‐IV (50 μ m , 4 h) during the postischemia period also obviously increased the expression of HIF‐1α, iNOS, and Bcl‐2 and reduced the caspase‐3 expression and LDH release in IRI cardiomyocytes and isolated heart . Under the hypoxia condition, AS‐IV (25–50 μg/mL/31.8–63.6 μ m ) demonstrated the potent protective effect of cardiomyocytes via upregulating the expression and the activity of SOD‐1 and inhibiting the ROS and MDA under the physiological and hypoxic status in the cytoplasm .…”
Section: Pharmacological Effect Of Astragaloside IVmentioning
confidence: 99%
“…We identified HIF‐1α as a partner that mediates MCPIP1 function in hepatic I/R injury. HIF‐1α is known to be a protective factor in human I/R injury and in multiple organ I/R injury models . For instance, a meta‐analysis demonstrated that HIF‐1α attenuated liver I/R injury .…”
Section: Discussionmentioning
confidence: 99%
“…HIF‐1α activation has been documented in multiple pathological conditions through different mechanisms . Particularly, HIF‐1α is a protective factor in hepatic I/R injury, and pharmacological stabilization of HIF‐1α protects against myocardial I/R injury . Interestingly, HIF‐1α is stabilized by MCPIP1 .…”
mentioning
confidence: 99%
“…Activated HIF-1 participates in cellular survival and apoptosis, as well as biological effects such as drug resistance. Overproduction of HIF-1 increases local inflammation and aggravates IR injury [23]. Interferon-γ (IFN-γ) is a secretive factor with the ability to induce macrophage iNOS production, the overproduction of which is important in pathological processes including inflammation and acute rejection [24].…”
Section: Discussionmentioning
confidence: 99%